Fighting fire with aid : development programs as counterinsurgency tool : evidence for Colombia (2017)
I study the causal effect of the development foreign aid implemented by the U.S. Agency for International Development (USAID) on the intensity of municipality-level conflict in Colombia, for the period 2009-2013. In order to address a potencial simultainety bias, I instrument the foreign aid with the interaction of the United States GDP and the potential interventions during the Malaria Eradication Campaigns (circa 1957). On the one hand, the results point out that the foreign aid reduced the insurgency associated to the left-winged guerrillas, especially FARC. On the other hand, the foreign had no effect on the violence associated to the criminal gangs (BACRIM). I provide qualitative evidence on two potential mechanisms: (i) Development programs rise the opportunity cost of fighting (opportunity cost effect); (ii) Foreign aid improves the trust and the information flows between civilians and the local institutions (hearts and minds). Finally, I provide empirical evidence to cast doubt on two alternative channels whose predictions cannot be reconciled with the results: (i) Foreign aid might increase the rents that can be looted by the insurgents (rapacity effect); (ii) Development programs might rise the targeted assassinations committed by insurgents as a response to the loss of bargaining power in an scenario of peace talks.